Critically Examining Emerging Issues in Community-Based Research: Challenges and Opportunities - Harsono, Iwan; Azizah, Azizah; Aziz, Nabila Hasnah (Journal Ligundi of Community Service, 2024)
Background. Community-based research (CBR) has gained significant traction as a method to involve communities in the research process, fostering mutual benefits and promoting social change. However, despite its growing popularity, CBR faces various emerging issues that can impact its effectiveness and sustainability. These issues range from methodological challenges to ethical concerns and practical implementation barriers. Purpose. This study aims to critically examine the emerging issues in community-based research, identifying the primary challenges and exploring potential opportunities for enhancing the effectiveness and impact of CBR. By addressing these issues, the study seeks to provide insights that can guide researchers and practitioners in optimizing their approaches to community-based research. Method. The research employed a mixed-methods approach, combining a comprehensive literature review with qualitative interviews. The literature review analyzed recent studies and theoretical discussions on CBR, while the interviews were conducted with experienced CBR practitioners, including researchers, community leaders, and policymakers. The data collected were thematically analyzed to identify common challenges and opportunities within the field. Results. The findings highlight several key issues in community-based research. Methodological challenges include difficulties in maintaining rigorous scientific standards while ensuring community participation. Ethical concerns revolve around power dynamics, informed consent, and the equitable distribution of research benefits. Practical barriers often involve funding constraints, logistical issues, and the sustainability of community engagement. Despite these challenges, the study identifies numerous opportunities, such as the potential for capacity building within communities, the promotion of social justice, and the creation of more relevant and impactful research outcomes. Conclusion. Community-based research presents both significant challenges and promising opportunities. Addressing methodological, ethical, and practical issues is crucial for the advancement of CBR. By leveraging the identified opportunities, researchers can enhance the effectiveness and sustainability of their community-based projects, ultimately contributing to more equitable and impactful research practices. The study underscores the importance of continuous dialogue and collaboration between researchers and communities to navigate the complexities of CBR effectively.